If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = p + 3 Reorder the terms: 18 = 3 + p Solving 18 = 3 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 18 + -1p = 3 + p + -1p Combine like terms: p + -1p = 0 18 + -1p = 3 + 0 18 + -1p = 3 Add '-18' to each side of the equation. 18 + -18 + -1p = 3 + -18 Combine like terms: 18 + -18 = 0 0 + -1p = 3 + -18 -1p = 3 + -18 Combine like terms: 3 + -18 = -15 -1p = -15 Divide each side by '-1'. p = 15 Simplifying p = 15
| 7x+x-4=7x+5 | | 4(y-6)/3 | | 23=n-5 | | 7(m-1)-3(5m+2)=-9(m+3)-10 | | -3x-(-7)=-1 | | 0.32=w-0.1 | | 4[1-(-5x-7)]=100x+144 | | -2(w-4)-(4+6w)=-9w | | .09x^2+.03=.21 | | 3x-(x+6)=-4(x+1) | | .3y+.5=.42 | | 44/4 | | 44/11 | | 36n^3=49n | | 3-4(4m-7)=-17 | | X+(3/4)=(-9/2) | | 3x^2+52x+12=0 | | 8x+9=6x+39 | | 8(x-6)=9+7x | | 22+20x=4x | | 5(0)-7x=-7(5+x) | | 7z+7-5z=9+z-3 | | 138.80=0.09x+3.80 | | 7x-13+9=2+x | | -8(-2m+10)=-9+8(10m-10) | | 7k^2+2=-37 | | (x/1)+(1/x)=61/30 | | x^2-4-3x=0 | | sqrt(2x+3)=5 | | 6(x-.08)-0.2(5x-4)=6 | | 4/5x-7=-1/5x-7 | | w^2-26w-42=0 |